1997
DOI: 10.3354/meps160109
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation of radionuclide 137Cs concentration in marine organisms with special reference to the effect of food habits and trophic level

Abstract: ABSTRACT. Although a number of measurements have been made on radiocesium concentrations in aquatic organisms, no clear agreement has been reached on the factors affecting accumulation of these radionuclides. Natural variations in the concentration of the long-lived artificial radionuclide '37Cs in marine organisms and factors affecting variations in marine fishes were investigated through long-term and systematic measurements in coastal waters of Japan from 1984 to 1995. Concentrations of 13' Cs were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 14 publications
9
49
2
Order By: Relevance
“…Thus, activities of 137 Cs in biota of less than 1 Bq kg -1 wet weight (Table 1) represent a concentration of radiocesium that is nearly three orders of magnitude greater than levels observed in seawater (by wet mass). This difference of three orders of magnitude is consistent with partitioning coefficients (K d ) observed for cesium in laboratory-scale studies using phytoplankton (Fisher, 1985), but it is larger than the radiocesium concentration factors of one to two orders of magnitude observed between marine fishes and seawater in a recent comprehensive study undertaken in Japan (Kasamatsu and Ishikawa, 1997). However, Kasamatsu and Ishikawa (1997) indicated that concentration factors approach three orders of magnitude between radiocesium in seawater and biotic concentrations in the highest trophic levels, particularly for organisms that consume large fish.…”
Section: G − B (T)(q)(y)(e)supporting
confidence: 69%
See 1 more Smart Citation
“…Thus, activities of 137 Cs in biota of less than 1 Bq kg -1 wet weight (Table 1) represent a concentration of radiocesium that is nearly three orders of magnitude greater than levels observed in seawater (by wet mass). This difference of three orders of magnitude is consistent with partitioning coefficients (K d ) observed for cesium in laboratory-scale studies using phytoplankton (Fisher, 1985), but it is larger than the radiocesium concentration factors of one to two orders of magnitude observed between marine fishes and seawater in a recent comprehensive study undertaken in Japan (Kasamatsu and Ishikawa, 1997). However, Kasamatsu and Ishikawa (1997) indicated that concentration factors approach three orders of magnitude between radiocesium in seawater and biotic concentrations in the highest trophic levels, particularly for organisms that consume large fish.…”
Section: G − B (T)(q)(y)(e)supporting
confidence: 69%
“…This difference of three orders of magnitude is consistent with partitioning coefficients (K d ) observed for cesium in laboratory-scale studies using phytoplankton (Fisher, 1985), but it is larger than the radiocesium concentration factors of one to two orders of magnitude observed between marine fishes and seawater in a recent comprehensive study undertaken in Japan (Kasamatsu and Ishikawa, 1997). However, Kasamatsu and Ishikawa (1997) indicated that concentration factors approach three orders of magnitude between radiocesium in seawater and biotic concentrations in the highest trophic levels, particularly for organisms that consume large fish. A similar factor of 300 was recently observed for the differences between water column 137 Cs activities and wetweight tissues of seals and porpoises in marine waters of the British Isles (Watson et al, 1999).…”
Section: G − B (T)(q)(y)(e)supporting
confidence: 69%
“…A number of studies have shown that 137 Cs biomagnifies through marine food chains (e.g., Calmet et al, 1992;Kasamatsu and Ishikawa, 1997;Watson et al, 1999;Heldal et al, 2003). More recently, Brown et al (2004), utilising a biokinetic modelling approach to the trophic transfer of 137 Cs in marine food chains, demonstrated biomagnification at lower trophic levels but not to the highest level, which was represented by the harp seal in their study.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, the tendency for Arctic marine food chains to be dependent on benthic and sea ice associated systems provides an efficient mechanism for the biomagnification of contaminants, while the longevity of marine mammals in these food chains allows for the potential accumulation of contaminants over long periods of time in these top consumers. Certain marine biota exhibit high uptake rates of radionuclides (e.g., Pentreath et al, 1982;Aarkrog et al, 1997;Brown et al, 1999), while radiocaesium ( 137 Cs) has been shown to biomagnify through marine food chains and therefore be found in high concentrations in marine mammals (Calmet et al, 1992;Kasamatsu and Ishikawa, 1997;Watson et al, 1999;Heldal et al, 2003). Together, these observations may have important consequences for Arctic marine ecosystems if significant levels of contamination occur.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is suspected that radiocesium in sinking particles was mainly associated with lithogenic materials as described before, another possible reason is that the cesium was partly assimilated by living organisms (e.g. Kasamatsu and Ishikawa, 1997). Fowler et al (1987) also reported that 137 Cs can become concentrated in fecal pellets.…”
Section: Form Of the Radiocesium Associated With Sinking Particlesmentioning
confidence: 99%